Rancang Bangun UI/UX dengan Metode Design Thinking pada Aplikasi Laundry Quick and Clean Berbasis Mobile - Putra, Anak Agung Adi Wiryya; Mahayani, Ni Komang Dewi; Tilman, Benedito Nidio Da Rosa Maia (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The purpose of this research is to develop a mobile-based laundry application with Design Thinking method and measure the level of user satisfaction through System Usability Scale (SUS) testing. As the popularity of laundry services increases, manual management becomes a significant challenge, such as inefficiency in recording and tracking orders. Therefore, this research offers an innovative solution by designing a Quick and Clean application that focuses on improving user experience (UI/UX) to simplify the management of laundry services. This research uses a Design Thinking approach that includes five stages: empathize, define, ideate, prototype, and test. The empathize stage involved interviews with 15 laundry service users to identify key needs and problems. The define stage mapped out the functional and non-functional requirements that formed the basis of the application design. The ideate stage produced a 16-page wireframe design, while the prototype stage produced an application model with UI design using Figma. The novelty value of this research lies in the application of the Design Thinking method in the context of laundry services, which is rarely applied in similar studies, as well as the integration of UI/UX design that emphasizes ease of use and operational efficiency. SUS testing shows an average score of 85.6 which falls into the Excellent category. This result indicates that the application design not only meets user needs but also provides a satisfying experience, contributing to the development of UI/UX standards in laundry business applications. Overall, this research has made a significant impact by presenting an application model that can improve the efficiency and quality of moobile-based laundry services. And this development makes it easier for further development to develop further.